Pyrolysis kinetics of keyboard plastic waste using thermogravimetric analyser to assess its energy potential - Panda, Achyut Kumar; Patnaik, Satyanarayan; Kumar, Sachin (Journal of Environmental Engineering and Landscape Management, 2022)
In this paper, the kinetic parameters of discarded computer keyboard plastic waste are estimated using thermogravimetric analysis (TGA) with four different non-isothermal kinetic models at a wide range of heating rates 5, 10, 15, 20, 40, 60 and 100 °C/min. The gross calorific value of waste computer keyboard plastic is 38.96 MJ/Kg. FT-IR analysis confirms the presence of alcohol, phenol, ether, ester, carboxylic acid, aromatic, and alkene compounds in keyboard plastic waste. The average values of activation energy are calculated as 158.1668, 198.883, 193.612, and 197.765 kJmol−1 from Kissinger, Friedman, FWO, and Coats-Redfern methods, respectively. The kinetic data obtained in this work would be useful for accurate prediction of reaction behaviour and in the design of efficient commercial process for the conversion of such plastic wastes to energy.